Programa para formação de agentes ambientais em centro penitenciário: plano de aproveitamento de resíduos sólidos convencionais - Moreno, Ronal Ariel Alvarez (2016)
Through this research it was possible to structure the Penitentiary Standard Santa Rita-PB, a non-formal education program for the training of environmental agents. The program is based on the awareness of convicts and dissipation of knowledge on environmental management, to achieve awareness and transformation in this population. In turn, subsequently, this population is multiplying the acquired knowledge. The program is divided into two cycles, consisting of modules (Cycle I: Introductory Module, Ecology and Environment / Soil and Water Cycle II:. Air Module, Sanitation, Waste Management, and Environmental law), lasting 48 contact hours, respectively. Two methodologies were applied, one for the use of conventional solid waste program and another for program creation. Each of these methodologies containing six phases. Data were collected through questionnaires and strategies were implemented in a participatory way, aiming at environmental awareness of reeducation in the sensitization process. Among the penitentiaries consulted only Penitentiary Standard Santa Rita-PB volunteered to participate, with 16 reeducation. It was noted an active participation and a serious commitment by the management and employees of the establishment, who supported all the time the proposed activities. Encouraged the participation and awareness is encouraged on environmental issues in the prison population, which was an important basis for developing this mission. It was delivered to establish an Environmental Training Program created, structured and composed. The results showed that the ways of environmental education are viable alternatives to the construction of knowledge among the convicts, who awakes ecological consciousness and may contribute to the reduction of social inequalities. It was concluded that by creating this program facilitates the environmental education learning process and that this tool can be used in the rehabilitation of convicts.